Analisis Model Kepemimpinan Kharismatik dan Visioner di Pondok Pesantren - Dede Ridho Firdaus; Khairunnisa Khairunnisa; Anis Zohriah; Anis Fauzi (Journal on Education, 2023)
This paper is a type of qualitative research with a library research approach. Collection of literature related to charismatic and visionary leadership. Furthermore, when viewed from the closeness of the content, the literature can be classified into two. First, the primary source (primary source) and the second secondary source (secondary source). Charismatic leadership is a leadership style by highlighting charisma to attract and inspire devotion by others. A visionary leader is a leader who is able to determine where the organization is going and how to achieve it. Thus, visionary leaders must have predictive, anticipatory, systematic, holistic, integrative, and comprehensive thinking skills.